A Novel Solid Substrate Room Temperature Phosphorimetry for the Determination of Trace Cytochrome C and Forecast of Human Diseases. (26th December 2012) - Zheng, Zhi-Yong; Cui, Ma-Lin; Liu, Jia-ming; Jiang, Shu-Lian; Jiao, Li; Zhang, Li-Hong; Lin, Xuan; Lin, Shao-Qin
Abstract : The reaction between fullerenol (F-ol) and cytochrome C (Cyt C) could be carried out to form a nonphosphorescence compound using tween-80 as photosensitizer which causes the sharp quenching of room temperature phosphorescence (RTP) of F-ol. Bearing this in mind, a novel solid substrate room temperature phosphorimetry (SSRTP) for the determination of trace Cyt C has been proposed in this study. Under the optimum conditions, the linear range of this method is 1.0 × 10 - 16 –2.4 × 10 - 14   g   mL - 1, which is directly proportional to Δ I p of Cyt C-F-ol–tween-80 system, and the detection limit (DL) is 3.0 × 10 − 17  g   mL - 1 . It has been applied to the determination of Cyt C in human serum and forecast of diseases, and the result matches with the enzyme-linked fluorescence immunoassay (ELISA). Meanwhile, the reaction mechanism of SSRTP for the determination of Cyt C and the enhancing effect of tween-80 on RTP of F-ol were also discussed.